Bacterial nanocellulose membranes as potential chronic wound dressing: influence of alternative culture media on nanofiber diameter - a brief review - Oviedo, Vinícius Rodrigues; Balbé, Fábio Portela; Rodrigues Jr., Luiz Fernando; Sagrillo, Michele Rorato; Fagan, Solange Binotto; Fernandes, Liana da Silva (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
Chronic wounds are a major health problem worldwide. Mainly associated with chronic diseases and aging, this condition decreases life quality and expectancy in patients. Biomaterials are a growing trend in the biomedical industry due to their composition includes substances and similar structures to the human body, what brings the possibility of discovery and use of certain protein bindings and other physiological signs that can aid in the healing and biointegration process. Bacterial nanocellulose is a biomaterial formed by an interlaced fitting of nanofibrils about 100 nm in diameter, making it an excellent material for chronic wounds dressings due to its specific characteristics, such as (i) liquid absorption capacity, (ii) high crystallinity, (iii) purity, (iv) three-dimensional structure, (vi) permeability to gases and (vii) biocompatibility. To overcome one of its limitations, - the absence of antimicrobial activity - there is the need of structural modifications. These modifications can be in-situ (during the membrane formation) or ex-situ (after the membrane formation), by physical (adsorption or absorption), or chemical (oxidation, esterification, etc.) methods. Another drawback regarding bacterial nanocellulose is the high cost of standard culture media during its production, which has been solved with alternative solutions. This review selected 8 papers in the PubMed and Science Direct databases, in which bacterial nanocellulose was obtained by using alternative media of culture, such as (i) kombucha, (ii) agro-industrial wastes, and (iii) fruit/vegetable peel wastes. The aim of this review is to overview how the production of bacterial nanocellulose in alternative media affects its nanostructure and crystallinity index.